استدراكات الشيخ الألباني على الشيخ سيد سابق من خلال كتابه تمام المنة في التعليق على فقه السنة - دراسة حديثية فقهية على بعض النماذج من باب كيفية الصلاة - سود شرف الدين (University of Eloued جامعة الوادي, 2024)
" الحمد لله وحده والصلاة والسلام على من لا نبي بعده، وبعد: هذا البحث بعنوان استدراكات الشيخ الألباني على الشيخ سيد سابق من خلال كتابه تمام المنة في باب كيفية الصلاة، وهي عبارة عن دراسة حديثية فقهية، حيث قمت بوضع خطة احتوت على مقدمة مشتملة على إشكالية البحث، وأهميته، وأسباب اختيار الموضوع، وأهداف البحث، ومنهج البحث والدراسات السابقة. ثم قسّمت العمل إلى ثلاثة مباحث: فالأول عبارة عن تعريفٍ بمفردات العنوان، والمبحث الثاني تناولت فيه استدراكات الشيخ الألباني على الفقهاء عموما، وأما المبحث الثالث تناولت فيه استدراكات الشيخ الألباني على الشيخ سيد سابق خصوصا، ثم خاتمة ذكرت فيها بعض النتائج التي توصلت إليها، والتي من أهمها مكانة الشيخ الألباني العلمية مما مكنه ذلك من نقد أقوال الفقهاء والاستدراك عليها، ثم ذكرت بعض التوصيات "All praise is to Allah and the blessing and peace be upon his last prophet, This study is entitled with "" Sheikh Al-Albani Remarks on Sheikh Sayyid Sabiq's book '' Tamam al-Minna "" in the chapter of : (How to Pray) .The study is a jurisprudential-hadith that addresses the following question: What are the places where Sheikh Al-Albani made remarks on the scholars of Fiqh? In order to answer this question, I put a plan with an introduction that includes the statement of the problem, its significance , the reasons for choosing the topic, the aims of the study , the study methodology, and literature reviews. I then divided the work into three chapters: The first one is general concepts. The second chapter deals with Sheikh Al-Albani's remarks on scholars of Fiqh in general, and the third chapter deals with Sheikh Al-Albani's remarks on Sheikh Sayyid Sabiq in particular, and then a conclusion in which I presented some of the study findings, the most important of which is Sheikh Al-Albani's scholarship status, which enabled him to criticize the scholars of fiqh. Finally, I concluded with some recommendations.
Keywords: استدراكات، الألباني، سيد سابق، تمام المنة، كيفية الصلاة.; Remarks; Al-Albani; Sayyid Sabiq; Tamam Al-mina; How to Pray.